Avian borna virus in psittacine birds : viral distribution, tropism and immune response - AL-Ibadi, Basim Ibrahim Hasan; Justus Liebig University Giessen (My University, 2015)
Avian Borna viruses (ABV) are the etiological agents for proventricular dilatation disease (PDD). Distribution patterns of ABV-2 and ABV-4 in experimentally ABV-2 and ABV-4 infected cockatiels were similar to distribution patterns of ABV in naturally PDD affected psittacines. ABV-2 and ABV-4 exhibited broad tissue distribution patterns in all organs in experimentally ABV-2 and ABV-4 infected cockatiels. Inflammatory lesions, ABV antigen, ABV-2 genome and ABV-2 mRNA were mainly detected in the gastrointestinal tract (GIT) and peripheral organs after ABV-2 infection. Inflammatory lesions, ABV antigen, ABV-4 genome and ABV-4 mRNA were predominantly detected in the central nervous system (CNS) and peripheral organs after ABV-4 infection. ABV-2 transcription was effective in the GIT organs after ABV-2 infection. ABV-4 transcription was operative in the CNS after ABV-4 infection. These findings indicate distinct differences in biological behaviour between the used ABV-2 and ABV-4 isolates. By immunohistochemistry, CD3-positive cells were detected in cellular infiltrations in all organs after ABV-2 and ABV-4 infection. Isolation of buffy coat (BC) cells of cockatiels and stimulation with phytohaemagglutinin (PHA-M) were successfully established. Characterization of CD3-positive cells, CD4-positive cells, CD8a-positive cells, monocytes, B cells, and thrombocytes was successful in cockatiel BC by indirect immunofluorescence. Characterization of CD4-positive cells, CD8-positive cells, monocytes, B cells, thrombocytes cells but not CD3-positive cells was possible in cockatiel BC by flow cytometry. ABV antigen and ABV-4 RNA were not found in BC cells of cockatiels from day 0 until day 15 post infection with ABV-4. Moreover, ABV antigen and ABV-4 RNA were not found in stimulated BC cells from day 0 until day 15 after stimulation and ABV-4 infection. These results providing first evidence that cockatiel blood cells could not directly be infected with ABV-4.Further investigations on the role of macrophages or endothelial cells for the dissemination of ABV infection within an infection are therefore required.

Aviäre Bornaviren (ABV) sind Auslöser der neuropathischen Drüsenmagendilatation (proventricular dilatation disease, PDD). Die Verteilungsmuster von ABV-2 und ABV-4 in experimentell ABV-2 und ABV-4 infizierten Nymphensittichen stimmten mit dem Verteilungsmuster des Virus in natürlich an PDD erkrankten Psittaziden überein. Die beiden Genotypen ABV-2 und ABV-4 nach experimenteller Infektion von Nymphensittichen ein breites Verteilungsmuster in allen Organen auf. Entzündliche Läsionen, ABV-Antigen, ABV-2-Genom und ABV-2-mRNA wurde hauptsächlich im Gastrointestinaltrakt (GIT) und in peripheren Organen nach ABV-2-Infektion festgestellt. Im Vergleich dazu wurden nach Infektion mit ABV-4 entzündliche Läsionen, ABV-Antigen, ABV-4-Genom und ABV-4-mRNA vorherrschend im zentralen Nervensystem (ZNS) und in peripheren Organen festgestellt. Nach ABV-2-Infektion läuft eine effektive Transkription des Virus vor allem im GIT ab, während es nach ABV-4-Infektion zu einer deutliche Transkription im ZNS kommt. Diese Ergebnisse zeigen, dass es deutliche unterschiede im biologische Verhalten zwischen den verwendung ABV-2 und ABV-4 Isolaten gibt. Mittels Immunhistochemie konnten nach ABV-2- und ABV-4-Infektion CD3-positive Zellen in den zellulären Infiltrationen in allen Organen festgestellt werden. Die Isolierung von Buffy-Coat (BC) Zellen von Nymphensittichen und ihre Stimulation mit Phytohämagglutinin (PHA-M) wurden in dieser Arbeit erfolgreich. Mit Hilfe von indirekter Immunfluoreszenz konnten CD3-positive Zellen, CD4-positive Zellen, CD8-positive Zellen, Monozyten, B-Zellen und Thrombozyten in BC Zellen Charakterisierung von Nymphensittichen werden. In der Durchflusszytometrie war die Charakterisierung von CD4-positive Zellen, CD8-positive Zellen, Monozyten, B-Zellen, und Thrombozyten, aber nicht von CD3-positive Zellen aus Nymphensittich BC möglich. Unsere Untersuchung zeigt weiterhin, dass kein ABV-Antigen und keine ABV-4-RNA in Buffy-Coat (BC) Zellen von Nymphensittichen im Zeitraum von 0 Tagen bis zu 15 Tagen nach einer Infektion mit ABV-4 gefunden wurden. Außerdem waren kein ABV-Antigen und keine ABV-4 RNA in stimulierten BC-Zellen von Tag 0 bis Tag 15 nach der Stimulation und ABV-4-Infektion nachweisbar. Diese Ergebnisse zeigt dass Nymphensittichblutzellen nicht direkt mit ABV-4 infiziert werden.Weitere Untersuchungen über die Rolle von Makrophagen oder Endothelzellen in der Verbreitung der ABV-Infektion innerhalb des infection wird erforderlich.
Keywords: ddc:630